2016
DOI: 10.3389/fpubh.2016.00282
|View full text |Cite
|
Sign up to set email alerts
|

A Guide to the Design of Occupational Safety and Health Training for Immigrant, Latino/a Dairy Workers

Abstract: Industrialized dairy production in the U.S. relies on an immigrant, primarily Latino/a, workforce to meet greater production demands. Given the high rates of injuries and illnesses on U.S. dairies, there is pressing need to develop culturally appropriate training to promote safe practices among immigrant, Latino/a dairy workers. To date, there have been few published research articles or guidelines specific to developing effective occupational safety and health (OSH) training for immigrant, Latino/a workers in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 85 publications
(157 reference statements)
1
28
0
Order By: Relevance
“…Training programs have been described for those involved in the parlor, calving management, hoof trimming, and reproduction management, as well as calf rearing. In addition, studies have been done of the employees themselves to better understand the audience, particularly for worker safety training programs for this audience (Menger et al, 2016). However, little has been reported about calf care employees specifically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Training programs have been described for those involved in the parlor, calving management, hoof trimming, and reproduction management, as well as calf rearing. In addition, studies have been done of the employees themselves to better understand the audience, particularly for worker safety training programs for this audience (Menger et al, 2016). However, little has been reported about calf care employees specifically.…”
Section: Discussionmentioning
confidence: 99%
“…Literacy levels, education, as well as language are important factors to consider when developing training programs (Arcury et al, 2010). When designing worker safety programs for the Hispanic audience, Menger et al (2016) summarized important considerations for effective training programs, included reading level, the avoidance of stereotypes, and the use of various strategies and learning aids to encourage comprehension. Juárez-Carrillo et al (2017) conducted focus groups with dairy employees to develop a program for farm safety.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some studies have reported significant positive effects of training in terms of increased farmworkers' knowledge of OSH issues [12,13], whereas other studies have found no differences between trained and untrained participants [14][15][16][17]. Some authors have interpreted these contrasting results in light of the need to adapt the training materials to an audience of migrants [10,[18][19][20], considering particularly the content, layout and style of the graphics [21], to make safety communication more effective. A relevant contribution to reach this aim may come from ergonomics and its user-centred perspective in system design [22].…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this is that when "researchers or developers use a narrower selection of usability measures for evaluating a system, they either (a) make some implicit or explicit assumptions about the relations between usability measures in the specific context or (b) run the risk of ignoring important aspects of usability" [32] (p. 351). In addition, it should be noted that most of this previous research regarding safety training for migrant farmworkers has dealt with the efficacy of training interventions addressing migrants of Latino/Hispanic origin in a US context [19]. However, the literature has overlooked other cultural contexts, such as Europe, despite it being characterised by a high heterogeneity of cultures, languages and important migration fluxes.…”
Section: Introductionmentioning
confidence: 99%
“…Among the farming population, there are specific types of workers, such as migrants, who are often employed in agriculture [22] and as such are exposed to occupational hazards and risks [23]. Low levels of education, diversity of language, young age and lack of experience are characteristics that differentiate the specific needs in terms of agricultural training and approaches to health safety training for this type of agricultural worker [24,25]. Apart from migrants, there are other populations that are affected by agriculture hazards, such as women and youth.…”
mentioning
confidence: 99%